PARADIGMA BARU PENDIDIKAN KONTEMPORER DI INDONESIA - Colle Said (Paedagogia: Jurnal Pendidikan, 2019)
Education is a series of processes of human empowerment towards maturity, both intellectually, mentally and morally, to carry out the humanitarian function carried as a servant (abd) in front of his Khaliq and as a "preserver" (caliph) in the earth. the position of contemporary education in the midst of the spirit of national education reform, of course it is necessary to look at the meaning and role of contemporary education in this national life. Similarly, in order to find a new paradigm of contemporary education, it should begin with the existence of Islamic education in the history of national and state life. And in developing the quality of contemporary education, of course it is necessary to pay attention. First, education is increasingly demanded to appear as emerging in the development of the quality of human resources (output of education). Second, in the perspective of the world of work, an orientation to real abilities (what one can do) that can be displayed by very strong education graduates Third, as a result of globalization.